2021
DOI: 10.3390/math9091058
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Optimal Investment Strategy in the Context of Pandemic Regional Lockdown

Abstract: The Covid-19 pandemic has generated major changes in society, most of them having a negative impact on the quality of life and income obtained by the population and businesses. The negative consequences have been highlighted in the decrease of the GPD level for regions, countries and even continents. Returning to pre-pandemic levels is a considerable effort for both economic and political decision-makers. This article deals with the construction of a mathematical model for economic aspects in the context of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The impact of income on purchase re-evaluation and maintenance of new shopping habits caused by the pandemic was not confirmed. The restrictions placed during the pandemic meant that enterprises in some sectors of the economy were not able to do their business as they did in the pre-pandemic period [45]. Thus, the influence of the economic sector needs to be verified.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of income on purchase re-evaluation and maintenance of new shopping habits caused by the pandemic was not confirmed. The restrictions placed during the pandemic meant that enterprises in some sectors of the economy were not able to do their business as they did in the pre-pandemic period [45]. Thus, the influence of the economic sector needs to be verified.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis shows that company's report (accounting and financial) involves the being of a financial state within the entity, which guaranties the repetition of reporting (Grigoras-Ichim & Morosan-Danila, 2020), while maintaining a certain level of worth that is the basis of the operation of taking the decision that responds rapidly to all modifications and problems posed by the business environment, by also the social and political ones, especially in regard to the economic activities affected by the COVID-19 crisis (Morosan-Danila & Bordeianu, 2020a, 2020bTonnoir et. al, 2021).…”
Section: Recommendation For Sustainability In a Crisismentioning
confidence: 99%
“…Past studies have suggested that companies will choose the optimal strategy to maximize corporate interests [18], and few companies may invest in non-profit environmental management [19]. However, companies can transform these non-profit investment experiences into the status of a senior management team (TMT) to influence the company's adoption of environmental management [20], and environmental strategy has been identified as a key source of competitive advantage [21,22].…”
Section: Goi and Pesmentioning
confidence: 99%